Numerical Study on Deformation Capacity of Steel Plate Reinforced Concrete Shear Walls - Zhi Zhou; Jiang Qian; Wei Huang (Advances in Civil Engineering)
Steel plate reinforced concrete (SPRC) shear wall consists of steel plate encased in the concrete, in which the material advantages of both concrete and steel are utilized. The lateral resistance and deformation capacity of the shear wall are greatly improved. This paper investigates the deformation capacity of the SPRC shear wall under cyclic loads. A nonlinear 3-D finite element model in ABAQUS was developed and validated against published experimental results. Then, a parametric study was conducted to obtain the yield and ultimate rotation of SPRC shear walls with flexural failure. By statistical analyses, formulas for the yield and ultimate rotation of SPRC shear wall were proposed.